Predicting Sexual Harassment From Hostile Sexism and Short-Term Mating Orientation: Relative Strength of Predictors Depends on Situational Priming of Power Versus Sex. (February 2018) - Diehl, Charlotte; Rees, Jonas; Bohner, Gerd
Previous research has shown that short-term mating orientation (STMO) and hostile sexism (HS) selectively predict different types of sexual harassment. In a priming experiment, we studied the situational malleability of those effects. Male participants could repeatedly send sexist jokes (gender harassment), harassing remarks (unwanted sexual attention), or nonharassing messages to a (computer-simulated) female target. Before entering the laboratory, participants were unobtrusively primed with the concepts of either sexuality or power. As hypothesized, sexuality priming strengthened the link between STMO and unwanted sexual attention, whereas power priming strengthened the link between HS and gender harassment. Practical implications are discussed.